Renewable Energy in Eastern North Africa in Terms of Patterns of Coupling to Czisch European HVDC Super Grid - Boubaker, K; Colantoni, A; Allegrini, E (International Journal of Renewable Energy Development, 2013)
In this study, wind energy potential and perspectives in the eastern North Africa region (Tunisia) have been investigated in terms of connectivity to the projected Czisch European HVDC super grid. A simplified extracted scheme of this grid has been used as a guide to optimize transportation efficiency through the whole net. Wind, as an available and easily exploitable renewable energy was showing to have a promising future for 2025 horizon in the context of a connected net with the European Union, despite local sub-grids disparities. This is also to emphasis HVDC technology adequacy for economical power transmission over very long distances and connection between differently established grids.